PELABELAN TOTAL (A,D)-SISI ANTIAJAIB SUPER PADA GRAF G + K_1 - Christyan Tamaro Nadeak (MATHunesa: Jurnal Ilmiah Matematika, 2025)
Let be a graph of order and size . A bijection is called -edge antimagic total labeling if the set of edge weight forms an arithmetic sequence with initial term a and difference d, or equals to the set . An -edge antimagic total labeling is called super -edge antimagic total labeling if the labelling of the vertex set is This study discuss a super -edge antimagic total labeling for graph .